2002
DOI: 10.1557/proc-754-cc10.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annealing and Annealing with Pressure on Devitrification of Al87Ni7Gd6

Abstract: The effects of annealing for 30 minutes at temperatures ranging from 123-232°C on the structure evolution, resulting hardness, and tensile properties were determined for amorphous ribbons of Al 87 Ni 7 Gd 6. Structure evolution was determined using a combination of XRD, DSC, and TEM, while micro-hardness and tensile testing of ribbon specimens was used to evaluate the mechanical properties. Significant effects of annealing on the evolution of structure and properties were obtained, while the superposition of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…It is well known that a broad peak in XRD spectrum indicates a state which loses the long-range ordering of atomic arrangements 39) . This is like liquid, what is called an amorphous state.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that a broad peak in XRD spectrum indicates a state which loses the long-range ordering of atomic arrangements 39) . This is like liquid, what is called an amorphous state.…”
Section: Resultsmentioning
confidence: 99%
“…The contributions from the crystalline and residual amorphous phases were fitted with a Lorentzian function. The volume fraction of Al nanocrystals was calculated using the relative areas of the convoluted amorphous halo, A am , and crystalline, A cr , peaks (111) and (200) as X=A cr /(A cr +A am ) [23]. As it has been shown earlier [18], an underestimation of X calculated by this technique [24] has no influence on the effective diffusion coefficient values.…”
Section: Methodsmentioning
confidence: 98%
“…Al-TM-RE (TM¼transition metals, RE ¼rare earth elements) amorphous alloys and their nanocrystalline counterparts possess high strength and bend ductility [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and are being explored as low density, high strength engineering materials. Among these systems, Al-Gd-Ni and Al-4Y-4Ni alloys have been well investigated with regard to their glass formability, devitrification behaviors, as well as mechanical properties [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Among these systems, Al-Gd-Ni and Al-4Y-4Ni alloys have been well investigated with regard to their glass formability, devitrification behaviors, as well as mechanical properties [4][5][6][7][8][9][10][11][12][13]. Investigations have showed that Al-Gd-Ni and Al-4Y-4Ni metallic glass ribbons containing 80-92 at.…”
Section: Introductionmentioning
confidence: 99%